The Causes Of Glossophobia In The Students Speaking Classroom - Mella Sahara; Ivan Achmad Nurcholis (Teaching English and Language Learning English Journal, 2022)
Glossophobia, also known as “fear of public speaking” is the feeling of fear while speaking in front of public, often characterized as fear of speaking publically or nervousness in communication. It is a feeling of panic related with different physiological changes like elevated heart and breathing rates, over-rapid reactions, trembling of muscles and shoulder and neck area stiffness among others. The objective of the research was to find out the causes of glossophobia of the students in speaking classroom at Study Program of Muhammadiyah Bengkulu. The design of this research was descriptive qualitative method. The instrument of the research was questionnaire 25 items. The results showed that there were three causes of the students’ glossophobia in speaking classroom at Study Program of Muhammadiyah Bengkulu they were: anxiety, fear and negative thinking. The dominant cause of the students’ glossophobia in speaking classroomat Study Program of Muhammadiyah Bengkulu was fear. They fear cannot give good performance, make mistake, not understand the material and cannot say something. So that, the other students laugh and humiliate their performance From the result, the researcher will give suggestion for the students: It is suggested the students can overcome their glossophobia to make their speaking perfomance be better. The students must be prepare all of component that support before speaking performance in the classroom such as understanding the material and often practice to make it perfect. Key words: Speaking, Glossophobia